OPTIMALISASI ASUPAN GIZI BALITA STUNTING MELALUI PELATIHAN PENYUSUNAN MENU SEIMBANG BERBASIS PANGAN LOKAL - Ni Putu Aryani; Baiq Ricca Afrida; Susilia Idyawati; Sri Hawari Jannati (Jurnal LENTERA, 2026)
Stunting in toddlers is a condition of growth failure due to chronic malnutrition over a long period of time, that can be made to prevent stunting include providing health education and training. The purpose of this community service was to provide information and training on preparing balanced menus based on local foods to mothers with toddlers. This activity was carried out in Lembar Selatan Village, Lembar District, West Lombok Regency, West Nusa Tenggara Province in September 2025. The target of this activity is 30 mothers with toddlers. The methods used are health education, discussion and training. The results of the measurement showed that there was an increase in understanding of mothers with toddlers about preparing balanced menus based on local foods by 40% (the average initial measurement value was 40 and the average final measurement value was 80). Attitudes also showed an increase of 38% and skills increased by 100%. This demonstrates that health education and training are effective in improving mothers with toddlers' understanding, attitudes, and skills regarding preparing balanced menus based on local foods